Dysfunctional types of eating behavior: sex differences, relationship with metabolic risk factors in individuals working in the Arctic on a rotating basis - A. S. Vetoshkin; N. P. Shurkevich; A. A. Simonyan; L. I. Gapon; M. A. Kareva (Кардиоваскулярная терапия и профилактика)
Aim. To study dysfunctional types of eating behavior (EB) in relation to metabolic risk factors in workers in the Arctic, as well as to determine sex differences.Material and methods. In the polar village of Yamburg (680 21’ 40 "N), 99 men (M) and 81 women (W) with grade 1 and 2 hypertension (HTN) and normal blood pressure, comparable by age (p=0,450), length of service in the north (p=0,956), number of rotation work years (p=0,824), office systolic BP (p=0,251), diastolic BP (p=0,579). The Dutch Eating Behavior Questionnaire (DEBQ) and questionnaires on scales of general and occupational stress were used. We conducted daily monitoring of blood pressure, carotid artery (CA) ultrasound to determine plaques. Biochemical blood tests were carried out with the determination of lipid profile parameters, circulating markers of nonspecific inflammation, levels of homocysteine, C-peptide, insulin, and cortisol.Results. The body mass index in 77% of men and women was determined above the norm, while class 1 and 2 obesity was found in 46% of M and 42% of W and negatively correlated with impaired dietary control (DC) in M (r=-0,305, p=0,045). Men were less resistant to stress (p<0,001). Most of the surveyed men and women had a low DC. In contrast to M, in W, correlations of DC with age (r=-0,374, p<0,001), stress level (r=0,394, p<0,001) were revealed. High DC in M was inversely associated with the level of C-peptide (r=-0,205, p=0,042); low DC — with cortisol level (r=-0,237, р=0,019). In W group, positive correlations were established between high DC and low-density lipoprotein cholesterol (r=0,265 p=0,016), apolipoprotein B (r=0,257, p=0,021), while glucose levels inversely correlated with low DC (r=-0,225, p=0,043). Men were characterized by lower emotionality of EB (Pχ2=0,026), which correlated with work experience (r=0,217 p=0,031) and body mass index (r=0,202, p=0,029), but higher external dependency of EB (Pχ2<0,001). According to logistic regression, the probability of HTN in W was higher with emotive control of EB, increasing the probability by 1,6 times: odds ratio (OR) =1,550, 95% confidence interval (CI): 1,046-2,297, p=0,029. The probability of plaque detect on CAs in M was higher with low DC: OR=0,470, CI: 0,257-0,860, p=0,014. In men with low DC, plaques were detected significantly more often than in women in CA (14 and 10%, Pχ2 = 0,034) and HTN (24 and 9%, Pχ2 = 0,019).Conclusion. Under the conditions of working in the Arctic on a rotating basis and psychophysical stress, most of the surveyed M and W had a low nutritional DC associated with overweight and class 1 and 2 obesity. Men, in contrast to women, were characterized by low emotionality and high external dependency of EB. Dysfunctional types of nutrition in M and W are associated with impaired carbohydrate and lipid metabolism, an increase in the level of inflammatory cytokines, which increased the probability of HTN in W and plaque detection in the CAs in M. The use of a simple DEBQ questionnaire for EB types in rotation workers can contribute to the early diagnosis of eating disorders and the prevention of CVD.